2023
DOI: 10.3390/molecules28083642
|View full text |Cite
|
Sign up to set email alerts
|

Potentiating Biosynthesis of Alkaloids and Polyphenolic Substances in Catharanthus roseus Plant Using ĸ-Carrageenan

Abstract: Catharanthus roseus is a medicinal plant that produces indole alkaloids, which are utilized in anticancer therapy. Vinblastine and vincristine, two commercially important antineoplastic alkaloids, are mostly found in the leaves of Catharanthus roseus. ĸ-carrageenan has been proven as plant growth promoting substance for a number of medicinal and agricultural plants. Considering the importance of ĸ-carrageenan as a promoter of plant growth and phytochemical constituents, especially alkaloids production in Catha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 112 publications
0
2
0
Order By: Relevance
“…The enhancement of AsA, TPC, and total antioxidant content in sprayed plants with biostimulantsbased amino acids might be correlated to the improvement of the photosynthesis system in plants which leads to the accumulation of secondary metabolites. Furthermore, several authors confirmed that foliar application with amino acid bio-stimulant plays an important role in antioxidant metabolism in plants (Hildebrandt et al, 2015;Weiland et al, 2015;El-Beltagi et al, 2023;Ramadan et al, 2023).…”
Section: Ascorbic Acid Total Phenol Content and Total Antioxidantsmentioning
confidence: 91%
“…The enhancement of AsA, TPC, and total antioxidant content in sprayed plants with biostimulantsbased amino acids might be correlated to the improvement of the photosynthesis system in plants which leads to the accumulation of secondary metabolites. Furthermore, several authors confirmed that foliar application with amino acid bio-stimulant plays an important role in antioxidant metabolism in plants (Hildebrandt et al, 2015;Weiland et al, 2015;El-Beltagi et al, 2023;Ramadan et al, 2023).…”
Section: Ascorbic Acid Total Phenol Content and Total Antioxidantsmentioning
confidence: 91%
“…The indole ( I-1 , R 1 = H, Figure ) scaffold is found in a wide range of bioactive heterocycles and natural products, such as vinblastine, vincristine, and plant growth regulator indolyl-3-acetic acid (IAA). Indole as a natural alkaloid is isolated from the clavicipitaceous fungus Balansia epichloe (Weese), which parasitizes pasture grasses . It also occurs in the oil of jasmine, cloves, and coal tar .…”
Section: Introductionmentioning
confidence: 99%
“…As well, it has antimicrobial, insecticidal, and antioxidative effects (Özcan and Chalchat, 2006;Afify et al, 2012) and carminative and mild expectorant characteristics of its essential oil were highlighted (El-Beltagi et al, 2020;Aly et al, 2023a). Furthermore, the role of anise oil in increasing the weight and the rate of conversion (FCR) of broiler hens was showed (El-Beltagi et al, 2023). Moreover, the aqueous extract of anise has a beneficial effect against neurological turbulence caused by lead intoxication (Ciftci et al, 2005).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%